Imaging anatomy of the lateral pelvic compartment applied to endometriosis - Pontes Fernandez, Cicília Fraga Rocha; Oliveira, Brunna Clemente; Franco, Izabela Pires; Matteoni-Athayde, Luciana; Ferreira, Ingrid Almeida Gomes; Brandão, Alice; Chamié, Luciana Pardini (Abdominal imaging, 2025)
Endometriosis impacts millions of women globally, making precise assessment essential for effective surgical planning and clinical management. Despite advances in transvaginal ultrasound (TVUS) and magnetic resonance imaging (MRI) for diagnosis and staging, many radiologists still overlook the evaluation of lateral pelvic anatomical structures. Understanding the lateral compartment's involvement is vital for accurate disease staging and achieving optimal surgical outcomes. This pictorial review provides a thorough examination of the lateral pelvic compartment anatomy using TVUS and MRI, complemented by surgical correlations. It offers detailed discussions on pelvic ligaments, parametrium, and adjacent structures, such as nerves, vessels, and ureters. The review provides practical guidance for identifying critical anatomical structures in imaging exams and emphasizes the importance of standardized terminology. Enhancing imaging precision and diagnostic accuracy for lateral compartment endometriosis is crucial for optimal surgical planning and improved patient outcomes.